La font de Llíria: Edició del primer milacre vicentí publicat (1822). - ZAPATA, JOAN VICENT FUERTES (Scripta)
The present work studies the first trext printed wich is considered a milacre (dramatic piece about Saint Vincent Ferrer). La font de Lliria was published anonymously in Valencia, in 1822, for the first time, and it is a sample of popular theater of the nineteenth century. It has been reedited on several occasions, and it has come to inspire later autors.